Cat Scratch Disease - Bhattacharjee, Swapna; Bhattacharjee, Shekhar; Montasir, Ahmed Al (Journal of Enam Medical College, 2012)
We report a case of cat scratch disease in a young boy who presented in the outpatient department of Enam Medical College Hospital, Savar, Dhaka with history of cat scratch and regional painful lymphadenopathy. The diagnosis was made on the basis of history, physical examination and common investigations including lymph node aspiration cytology DOI: http://dx.doi.org/10.3329/jemc.v2i1.11928 J Enam Med Col 2012; 2(1): 40-42